Pelatihan Interactive English Speaking Games untuk Meningkatkan Kepercayaan Diri Berbahasa Inggris Peserta Didik Anak Jalanan Kelas X di Yayasan Insan Mandiri Kota Depok - Ratna Wulandari; Aswarini Sentana; Anindia Ayu Rahmawati; Adani Nur Sabrina; Septian Dwi Putri; Ricky Perdana; Stella Amanda; Marliana Marliana (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Lack of self-confidence is the primary psychological barrier for street children in mastering English speaking skills. This community empowerment research, employing a quasi-experimental design, aims to enhance the English-speaking confidence of grade X street children at the Insan Mandiri Foundation, Depok, through Interactive English Speaking Games. The program was conducted from March to June 2026, involving a saturated sample of 45 tenth-grade students. The research design utilized a One-Group Pretest-Posttest Design executed over 12 intensive sessions. The intervention was developed based on scaffolding principles using various interactive games, such as Word Chain, Situational Role-Play, and Two Truths and a Lie. Evaluation metrics were collected via a modified Foreign Language Classroom Anxiety Scale (FLCAS) self-confidence questionnaire and a speaking performance rubric. The pre-test results revealed that the majority of students fell into the